Diskusi Kelompok Bernilai: Kunci Keaktifan dan Kemampuan Menulis Teks Tanggapan Siswa VII SMP - Sumarni Sumarni (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
The ability to write response texts is an important skill for junior high school students. This ability can help students to understand and communicate their ideas clearly and effectively. However, based on observations and data obtained from teachers, many junior high school students experience difficulty in writing response texts. This can be seen from the low scores of students in the response text material. This research aims to increase the activeness and ability to write response texts of class VII students at SMPN 24 Makassar through value-added group discussion methods. This research uses a classroom action research design with 4 cycles. The research subjects were students. Data was collected through observation, rubric assessment, and interviews. The research results show that the value-added group discussion method can increase students' activeness and ability to write response texts. This increase can be seen from the increase in student participation in group discussions, the frequency of expressing opinions and ideas, the frequency of asking questions, student focus and attention, the quality of the response text framework, the quality of paragraph development, and the quality of language use. The findings of this research indicate that the value-added group discussion method can be an effective alternative learning method to increase students' activeness and learning ability in Indonesian language subjects, especially response text material.